2018
DOI: 10.5195/d3000.2018.83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of root canal length measurement methods in primary teeth

Abstract: Objectives: The purpose of this study was to evaluate the accuracy of conventional radiography, intraoral digital radiovisiography and electronic apex locator in determining the working length of root canals in primary teeth (in-vivo) and to compare the results with scanning electron microscopy measurements (ex-vivo). Materials and Methods: This study was conducted on 50 primary molar teeth. Standard endodontic access cavity preparations were prepared and the actual length was calculated by calibrated investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In the sensitivity analysis, when considering only studies that were evaluated as 'low risk of bias' (Bhat et al, 2017;de Alencar et al, 2019;Oznurhan et al, 2015 difference between the electronic and radiographic measurements was −0.63 (95% CI [−1.15 to −0.10]; p = .02) (Figure S2). Nine studies were included for the radiovisiographic method (Abdullah et al, 2016;Awasthi et al, 2017;Balaji & Pravallika, 2019;Davalbhakta et al, 2021;Koruyucu et al, 2018;Kumar et al, 2016;Neena et al, 2011;Saritha et al, 2012;Wankhade et al, 2013), two for SEM (Koruyucu et al, 2018;Patino-Marin et al, 2011), and four for the visual direct method (Alafandy, 2018;Kumar et al, 2016;Senthil et al, 2016;Wankhade et al, 2013). The analysis showed that the electronic measurement did not differ statistically from the radiovisiographic method (−0.09; 95% CI [−0.22 to 0.04]; p = .20), SEM (−0.16; 95% CI [−0.83 to 0.50]; p = .63), and visual direct method (−0.05; 95% CI [−0.36 to 0.26]; p = .75).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the sensitivity analysis, when considering only studies that were evaluated as 'low risk of bias' (Bhat et al, 2017;de Alencar et al, 2019;Oznurhan et al, 2015 difference between the electronic and radiographic measurements was −0.63 (95% CI [−1.15 to −0.10]; p = .02) (Figure S2). Nine studies were included for the radiovisiographic method (Abdullah et al, 2016;Awasthi et al, 2017;Balaji & Pravallika, 2019;Davalbhakta et al, 2021;Koruyucu et al, 2018;Kumar et al, 2016;Neena et al, 2011;Saritha et al, 2012;Wankhade et al, 2013), two for SEM (Koruyucu et al, 2018;Patino-Marin et al, 2011), and four for the visual direct method (Alafandy, 2018;Kumar et al, 2016;Senthil et al, 2016;Wankhade et al, 2013). The analysis showed that the electronic measurement did not differ statistically from the radiovisiographic method (−0.09; 95% CI [−0.22 to 0.04]; p = .20), SEM (−0.16; 95% CI [−0.83 to 0.50]; p = .63), and visual direct method (−0.05; 95% CI [−0.36 to 0.26]; p = .75).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Inter-and intra-examiner agreement was assessed only in 11 studies, in which values were considered excellent for all analyses used: Kappa (0.87 to 0.98) (Davalbhakta et al, 2021;Koruyucu et al, 2018;Kumar et al, 2016;Odabaş et al, 2011), ICC (0.80 to 0.99) (Alafandy, 2018;Hafiz, 2018a;Patino-Marin et al, 2011;Wankhade et al, 2013), Cronbach's alpha (0.95 to 0.99) (Alafandy, 2018;de Alencar et al, 2019), and Altmann & Bland (0.98) (Kielbassa et al, 2003).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic apex locator methods give accurate root canal length when compared to other methods (24). Working length determination is an important factor for the success of root canal treatment, the canal should be prepared till the apical constriction or apical foramen 25 . The use of arbitrary Working length in anxious children is to reduce the duration of treatment for better cooperation from the child and to improve the quality of the treatment.…”
Section: Introductionmentioning
confidence: 99%